Organisational factors influencing early clinical trials enrollment: Gustave Roussy experience. (July 2018) - Besle, Sylvain; Schultz, Emilien; Hollebecque, Antoine; Varga, Andreea; Baldini, Capucine; Martin, Patricia; Postel-Vinay, Sophie; Bahleda, Rastislav; Gazzah, Anas; Michot, Jean-Marie; Marabelle, Aurélien; Angevin, Eric; et al.
Abstract: Purpose: Enrolment process influences the likelihood of patients' inclusion in early clinical trials (ECT) through social, medical and organisational factors. Patients and Methods: All patients referred from 2008 to 2016 to the Drug Development Department (DITEP) of Gustave Roussy (GR) were reviewed. Referring physician, organisational factors, medical and socioeconomic characteristics for patients were analysed. Multivariate analysis was performed with regard to those factors. A telephone survey was conducted on a sample of referring physicians located outside GR (N = 142). Results: Between 2008 and 2016, 8694 requests were received with 49% from external physicians. Here, 4517 were male patients with a median age of 58 [49–66] years (range 18–85). Tumour types were gastrointestinal (28%), lung (19%), breast (9%) and gynaecologic (8%). Mean enrolment rate was 37% (ranging from 24 to 45%). From 2008 to 2016, the enrolment rate decreases from 39% to 24%. In the meantime, DITEP trials portfolio evolves with the part of precision medicine trials increase from 12% to 40%. Factors that were significantly associated with a lower likelihood of being enrolled were referral from an external physician (OR 0.15 s.16–0.21]) compared to a physician from DITEP and year of the request (2.74 [1.8–2.9] 2008 versus 2016). The enrolment rate and the number of patients addressed have a high variability regarding referring physicians, which is little explained by characteristics as training, previous experience or attitude regarding ECT. Conclusion: Beyond patients' individual characteristics, we show that organisational and professional factors have a major impact on likelihood of enrolment in ECT. Highlights: Gustave Roussy's early phase trials unit (DITEP) enrols patients throughout France with a formalised recruiting process. The number of requests increased from 268 in 2008 to 1751 in 2016. The enrolment rate decreased from 39% in 2008 to 24% in 2016. Biomarker trials increased in DITEP's trials portfolio from 12% in 2008 to 40% in 2016. Patients referred from outside the DITEP are less likely to be enrolled.